Analisis Integrasi Keterampilan Abad Ke-21 Dalam Sajian Buku Teks Fisika SMA Kelas XII Semester 1 - Erlina Yusliani; Hanana Laila Burhan; Nurul Zakiatin Nafsih (JURNAL EKSAKTA PENDIDIKAN (JEP), 2019)
The 21st century education requires students to be able to think critically, collaboratively, communicate, be creative and innovate. The Indonesian government made efforts to address the demands of 21st century education by developing a 2013 curriculum that contained 4C skills. The learning process requires a textbook as a learning research. Learning textbooks circulating are not in accordance with 2013 curriculum criteria to improve 4C skills. The purpose of this study is to find out the Physics of Learning Textbooks for Class XII High School Semester 1 able to facilitate the implementation of 4C skills in the 21st century. This research is a descriptive study with a qualitative approach. The population of the data in the study were all physics of learning textbooks for class XII High School Semester 1. The sample was taken by using purposive sampling technique. The sample in this study was 5 Physics of learning Textbooks for Class XII High School Semester 1. The data in the study were taken using a questionnaire instrument. Based on the research that has been done, it can be concluded that the average for each component of 4C Skills, namely critical thinking skills (C1) obtained by 85, collaboration skills (C2) by 93.57, communication skills (C3) by 78.50 and creative thinking and innovation skills (C4) by 65.45.